Effects of Intellectual Capital (IC) on Return on Assets (ROA): Empirical Evidence from the Nigerian Oil Marketing Companies - Adamu Saleh, Ibrahim; Rabiu Mohammed , Mohammed; Kallamu Hassan, Musa (Kashere Journal of Humanities, Management and Social Sciences, 2022)
This paper examined the impact of intellectual capital (IC) on Return on Assets (ROA) of the listed Nigerian oil marketing companies for the periods January, 2005 to December, 2016. Return on assets (ROA) was used as proxy; while market to book value ratio (MB), Calculated Intangible Value (CIV), monetary model of Tobin’s Q (MMQR), Return model (RM), and Value Added Intellectual Coefficient (VAIC) were adopted to measure the IC. Other control variables used are physical assets intensity, financial leverage and size. Using ten years audited financial statements of six firms, filtered from the ten companies listed in 2016; the Pearson correlation, ordinary least square and fixed effect regression were used to analyze the data. The results indicate a significant relationship between the variables. The results in model one, MB, RM and VAIC were found to be positively and significantly correlated with ROA. These results have practical as well as policy implications of influencing investment decisions by the listed companies, existing/potential shareholders, other investors and the policies of companies in terms of investment in intellectual capital. They also have theoretical implication of supporting the arguments of knowledge-based theory; and regulatory implications, in form of the need to standardize IC reporting in Nigeria and other parts of the world. The study’s recommendations, therefore, centres on the maximization of total market valuation, maximization of IC return and increased investment in IC components by the quoted oil marketing companies.